Research and social change : a relational constructionist approach - McNamee, Sheila (Routledge advances in research methods, 2012)
This book bridges scholarly forms of inquiry and practitioners' daily activities. It introduces inquiry as a process of relational construction, offering resources to practitioners who want to reflect on how their work generates practical effects. There are hundreds of books on research, but in keeping with social scientific traditions, many emphasize method and neglect broader, overarching assumptions and interests. Further, most are written in ways that speak to those in the academic community and not to a wider audience of professionals and practitioners. The present text lays out relationa.